You are on page 1of 24

1

2

3

4

• 1 n + 1

n

=

1

n

+

1

n

1

2

3

4

n

n →∞

# 0 u 1
u 2
u 3
u 4
s 2
s 4
s 3
s 1

n → ∞

n

n

→ ∞

n

=

1

2

m

m

m

=

0

0

1

2

2

n

n

m

m

=

0

0

m

0

1

0

2

0

2

x

2

3

3

5

m

→ ∞

m

n

=

1

n

0

n

n

2

3

n = 0

n

+

1

n

+

1

n

n

n

= 0

n

2

3

n

+

1

n

+

1

n

n

n = 0

n

2

3

n = 0

n

n

0

1

2

2

n → ∞

n

+

1

n

+

1

n

n

n → ∞

n

+

1

n

n → ∞

n

+

1

n

# R = 1
lim
n
a
n
n → ∞

n = 0

n

3

6

9

3 n

n

2

3

# lim

n → ∞ n
a
8
1
n
+
1
=
=
n
+
1
a
8
8
n

k

=

0

k

k

01

2

2

k

k

1

k

=

1

12

3

2

k

=

2

k

k

2

23

2

x

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

2

1

2

k

=

0

k

k

01

2

2

k

k

1

k

=

1

12

3

2

k

=

2

k

k

2

23

2

3

4

2

5

3

0

1

2

2

3

3

2

0

2

0

3

1

3

1

4

2

4

2

0

5

3

5

3

1

0

1

2

2

0

2

1

3

0

4

1

5

0

1

2

4

3

5

0

0

1

1

0

1

0

2

0

2

k

k

=

0

m

+

k

k

=

0

k

mk1

+ −

k

=

0

k

mk2

+ −

k

=

0

k

mk1

+ −

kk

mk1

+ −

m

+

k

k

=

0

k

=

0

k

mk1

+ −

k

=

0

k

m

+

k

m

1

0

0

k

=

0

k

mk1

+ −

k

=

0

k

m

+

k

m

1

0

1

0

m

+

1

2

1

2

1

m

+

2

3

2

2

1

0

2

0

3

0

# 480

2

3

1

0

## 480

### Ms. Deepali Gupta. JIIT, NOIDA 1
For m =
3
1
a = −
a
1
0
4
1
1 3
Hence for m =
, y
=
a
x
⎜ ⎛
1
2
0
3

2

0

3

• 1680 0

2

3

# Thus complete solution is

1

2

2

3

0

## x 1 3

2

• x 3